The Relationship between Narrative Ability and Literacy in Grade 2 Elementary School Children in Surakarta - Az Zahidah, Farah Wafa; Sutanto, Alfiani Vivi; Wiliyanto, Dian Atnantomi (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Narrative is a type of discourse that aims to clearly describe to the reader an event that occured at a given time. To write a narrative is to recount an event or fact that occured at a given time, using written language. Such storytelling activity can help improve literacy. Literacy refers to an individual's capacity to comprehend and interpret information via reading and writing tasks. Students possessing proficient reading and writing abilities will find it easier to understand and articulate their thoughts. This study aimed to ascertain the correlation between storytelling skills and literacy among second-grade primary school pupils in Surakarta. This study employed a quantitative research methodology with a cross-sectional design and included one test. Data were gathered through story and literacy assessment sheets. The sample was acquired by quota sampling methods, comprising 50 individuals. The data analysis employed the parametric Shapiro-Wilk statistical and Spearman's Rank correlation tests. According to the data analysis findings utilizing Spearman's rank, the p-value (Sig.) is 0.002, indicating that p<0.05; thus, we may conclude that a significant link exists between storytelling skill and literacy. A correlation exists between narrative proficiency and literacy among second-grade elementary students in Surakarta.